Dynamic response of double beam rested on stochastic foundation under harmonic moving load. (21st September 2013) - Mohammadzadeh, Saeed; Esmaeili, Morteza; Mehrali, Mohammad
SUMMARY This paper deals with the dynamic response of infinite double Euler–Bernoulli beam supported by elastic foundation with stochastic stiffness subjected to an oscillating moving load, which is the first research in relevant literature review. In this matter, equations of motion for double beam are formulated in a moving frame of reference. Moreover, by employing the first order perturbation theory and calculating contour integration, the response of double beam is obtained analytically and validated by a stochastic finite element model. Sensitivity analyses on the various parameters of closed form solution such as velocity, load frequency, coefficient of variation of soil foundation and rail and slab bending stiffness show the significant effect of load frequency on the dynamic response of the doubled beam. From practical point of view, the obtained results of the present study can be utilized efficiently in analysis and design of slab track systems. Copyright © 2013 John Wiley & Sons, Ltd.